'Where do I go from here?': learning to become activist teachers through a community of practice. (4th March 2018) - Oliver, Kimberly L.; Luguetti, Carla; Aranda, Raquel; Nuñez Enriquez, Oscar; Rodriguez, Ana-Alycia
ABSTRACT: Background : Student-Centered Inquiry as Curriculum (SCIC) is an activist approach [Oliver, K. L., and H. A. Oesterreich. 2013. Student-Centered Inquiry as Curriculum as a Model for Field-Based Teacher Education. Journal of Curriculum Studies 45 (3): 394–417. doi:10.1080/00220272.2012.719550] inspired by years of research with youth. It was designed as a means of listening and responding to youth in order to better facilitate students' interest, motivation, and learning in physical education settings. While we have a strong and growing body of activist research with youth in physical education, SCIC as a specific approach to working with youth is in its infancy; thus, there is a need to further explore the challenges teachers/researchers face learning to use this approach to teaching. Purpose : This study explores how educators, in different contexts, learn to use an activist approach called SCIC, in order to better facilitate students' interest, motivation, and learning in physical education and physical activity settings. Research setting and participants : Participants included a university professor, a college instructor, a postdoctoral student, a doctoral student, and a pre-service teacher. Data were collected between January and May 2016. Data collection and analysis : Data collection included weekly field notes and debriefings following observations, teacher artifacts, weekly collaborative group meetings, and two individual interviews per teaching participant. Discussion and conclusions : The main challenge that emerged was learning how to move from a theoretical understanding of student-centered pedagogy to the practice of student-centered pedagogy. Specifically, the amount of time that was necessary to build a foundation that allowed for student and teacher understanding, respect, and comfort, negotiating teacher and student assumptions that were embedded in the status quo of physical education (PE), and the struggle to gather and use meaningful data to guide pedagogical decisions. We negotiated these challenges through our professional learning community whereby we worked to all be able to see and name what was happening in our individual classes and collectively planned what was needed to move forward through these challenges.